Di Perantauan Terhimpit, Di Negara Sendiri Terjepit: Reintegrasi Repatrian Suriname Di Tongar, 1954-1959 - Suparmi, Suparmi (Universitas Gadjah Mada, 2024)
Reintegration is an integral part of the study of repatriation. Each repatriate or group has unique and challenging reintegration experiences. This article aims to analyse the social and economic reintegration processes of Surinamese repatriates in Tongar (1954–1959). By employing the historical research method, which involves four stages—heuristics, source criticism, interpretation, and historiography—it reveals that, despite thorough planning, Surinamese repatriates in Tongar encounter difficulties in their economic and social reintegration. Economic challenges, such as limited capital and external factors, impede the initial reintegration process. They addressed these challenges by utilising available resources effectively and pursuing government loans. Simultaneously, language barriers and poor communication infrastructure create significant challenges for social reintegration. Most Surinamese repatriates, especially those children who were born and raised in Suriname, still lack proficiency in Indonesian. Through their daily interactions, the language barrier slowly lessened as they learned Indonesian and Minang. However, insufficient irrigation and a lack of medical personnel in Tongar continued to prevail, along with the rise of the Revolutionary Government of the Republic of Indonesia (Pemerintahan Revolusioner Republik Indonesia, PRRI) movement in West Sumatra, further complicating the reintegration process.